Design of readout circuit for piezoresistive pressure sensor using nodal array approach reading technique - Wan Zuha, Wan Hasan; Fairuz Rizal, Mohamad Rashidi; Mohd Nizar, Hamidon; Yufridin, Wahab (UPM Press, 2017)
In this paper, we proposed a new readout circuit in order to improve measurement output while reading the grouped resistive value in matrix array form. The purpose of having this circuit is to overcome the main problem in applying piezoresistive pressure sensor array for foot plantar application. This new approach is called Nodal Array Approach (NAA), a modified version of Wheatstone Bridge Circuit based on nodal analysis technique using Kirchcoff Current Law. The NAA calculates the sensors’ resistance values by solving simultaneous equations from reading voltages of the proposed readout circuit. Therefore, it is found that the readout circuit connection is of low complexity as it only uses resistive element as the major component of reading technique with only four iterations involved for each voltage nodes. Through simulation results, it shows that NAA is able to achieve high accuracy in obtaining a sensor’s resistance value by adhering to several limitations in order to avoid miscalculation (< 5% average calculation error).